2001
DOI: 10.1538/expanim.50.33
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Drug Metabolism-Related Enzymes by Methylcholanthrene and Phenobarbital in Transgenic Mice Carrying Human Prototype c-Ha-ras Gene and Their Wild Type Littermates.

Abstract: Transgenic mice hemizygously carrying human c-Ha-ras proto-oncogene, TgrasH2 show very sensitive and facilitated carcinogenicity to various carcinogens. In this study, activities of certain enzymes related to drug metabolism and energy metabolism were measured in microsome and cytosol fractions of livers of Tg-rasH2 mice and their wild type littermates with both sexes treated with 3-methylcholanthrene (MC) and phenobarbital (PB). Aminopyrine N-demethylase activities increased significantly in livers of all mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…No significant differences between the transgenic animals and their wild-type littermates were found for total hepatic CYP content, protein levels of distinct CYP isoforms, and for different CYP-related enzyme activities [42]. Accordingly, CYP activities were comparable between both male and female RasH2 transgenics and the respective wildtype controls [43]. These results were largely confirmed by a subsequent study in which no significant differences in CYP expression between RasH2 mice and wild-type controls were found.…”
Section: Regulation Of Cytochrome P450s By Egf/ Ras/ Mapk Signaling -mentioning
confidence: 56%
See 2 more Smart Citations
“…No significant differences between the transgenic animals and their wild-type littermates were found for total hepatic CYP content, protein levels of distinct CYP isoforms, and for different CYP-related enzyme activities [42]. Accordingly, CYP activities were comparable between both male and female RasH2 transgenics and the respective wildtype controls [43]. These results were largely confirmed by a subsequent study in which no significant differences in CYP expression between RasH2 mice and wild-type controls were found.…”
Section: Regulation Of Cytochrome P450s By Egf/ Ras/ Mapk Signaling -mentioning
confidence: 56%
“…Moreover, striking analogies in the transcriptome profiles of periportal hepatocytes and Ha-Ras-mutated mouse hepatoma cells indicate an important role of Ras signaling in the regulation of the periportal hepatocyte phenotype [4]. However, transgenic expression of Ha-ras or HGF led to conflicting results: whereas over-expression of HGF or mutant Ha-Ras (in the Tg lox(pA)H-ras* mouse) was effective in blocking basal CYP expression [5,49], two other Ha-Ras-transgenic mice (tg.AC and RasH2) did not show altered CYP expression [42][43][44]46]. In tg.AC mice, expression of the mutant Ha-Ras transgene is under control of the embryo-specific -globin promoter, and, as a consequence, expression of the transgene is lost in adult liver [45].…”
Section: Mapk-mediated Alterations Of Basal Cyp Expression In Murine mentioning
confidence: 84%
See 1 more Smart Citation
“…It is shown here that Sahh is induced by dioxin. Previous work has shown that liver Sahh activity is increased in mice exposed to 3-methylcolanthrene, another ligand for the AhR (Ohnishi et al 2001). Up-regulation of Sahh by dioxin might facilitate the collective activities of all methylation reactions in the cell by removing feedback inhibition, thereby affecting an array of biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The major target organs of DEN are the liver, lung, forestomach and hematopoietic system [12]. In our previous reports, Tg-rasH2 mice were characterized by stable activities of some enzymes related to drug detoxication and energy metabolism in their livers and kidneys compared to those in the non-transgenic control [18]. On the other hand, it has been reported that activities of enzymes in the glycolysis and the pentose phosphate pathway are significantly increased in developed tumor cells [1,7,17].…”
mentioning
confidence: 99%